From nature to abstraction: tensions between temporalities in the Land Law and its regulation (1850 – 1855): Da natureza à abstração: tensões entre temporalidades na Lei de Terras e sua regulamentação (1850-1855) (Revista de História da UEG (REVHIST), 2023)
The article aims to discuss how the Land Law (1850) and the Decrees and Notices aimed at its regulation are located between different historical times, between continuities and ruptures in the relationship with land. The legislators of the Brazilian imperial state, in their attempt to establish public lands as commodities, necessarily had to deal with the distinct temporalities of the landholding structure in the country, besides the internal contradictions of the commodification process itself. In this confluence of times, new conceptions emerged not only about lands, but also about nature. In the process of commodification, nature began to be measured, quantified, geometrized, and thus occurring the abstraction of its qualitative elements. Keywords: Land Law. Historical times. Commodity. Nature. Abstraction.